Differential tissue development compromising the growth rate and physiological performances of mussel. (September 2022) - Pérez-Cebrecos, Maitane; Prieto, Daniel; Blanco-Rayón, Esther; Izagirre, Urtzi; Ibarrola, Irrintzi
Abstract: Differences in the food acquisition rates and in the energetic costs of metabolism seem to affect the growth rate variability of mussels. The aim of this study was to analyze if the physiological performances responsible for such growth rate variability are accompanied by structural differences at tissue or cellular level in the main organs involved in energy acquisition (gill) and processing (digestive gland). Fast growers had higher cilia density and metabolic efficiency in their gill, and well-developed digestive tissue with barely no connective tissue or atrophy. Slow-growing mussels displayed stress signs that impede the proper acquisition, digestion and absorption of food: low cilia density, low mitochondrial capacity and high antioxidant activity levels in the gills, and high atrophy of the digestive gland. The data herein explains the growth rate variability of mussels, demonstrating that morphological and functional differences exist between fast and slow growers. Highlights: Slow growing mussel have lower clearance rate and metabolic efficiency than fast growers. Cilia density, together with gill area, explain the size-related differences in clearance rate. Gills of slow growers show higher antioxidant activity. Slow growers have less effective tissue to process food in the digestive gland. Degeneration in the tissues impedes growth and reserve accumulation in slow growers.